2009
DOI: 10.1016/j.niox.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

What is the real physiological NO concentration in vivo?

Abstract: Clarity about the nitric oxide (NO) concentrations existing physiologically is essential for developing a quantitative understanding of NO signalling, for performing experiments with NO that emulate reality, and for knowing whether or not NO concentrations become abnormal in disease states. A decade ago, a value of about 1 μM seemed reasonable based on early electrode measurements and a provisional estimate of the potency of NO for its guanylyl cyclase-coupled receptors, which mediate physiological NO signal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
286
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(309 citation statements)
references
References 166 publications
20
286
1
2
Order By: Relevance
“…The from NO donor. Although we did not quantify the NO molar concentration released by both NO donors, in accordance our findings, Hall and Garthwaite [38] reported that low NO concentration, a range of 100 pmol/L (or below), seems contribute to selective in vivo sGC activation.…”
Section: Resultssupporting
confidence: 85%
“…The from NO donor. Although we did not quantify the NO molar concentration released by both NO donors, in accordance our findings, Hall and Garthwaite [38] reported that low NO concentration, a range of 100 pmol/L (or below), seems contribute to selective in vivo sGC activation.…”
Section: Resultssupporting
confidence: 85%
“…The local concentrations of heat-induced nitrogen oxides at the point of the collapse of a nanobubble can be substantial. Importantly, some recent estimates place physiological • NO concentrations in vivo in the low nM range and below [48].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the actual circulating levels of nitrite in humans have been difficult to measure due to sampling problems and the poor performance of analytical assays. Despite highly sensitive methods have already been proposed, these are fairly cumbersome and not practicable for non-laboratory settings [4,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%